Skeletal muscle oxidative adaptations following localized heat therapy - Mohammed Ihsan; Mariem Labidi; Sebastien Racinais (European Journal of Applied Physiology, 2023)
Repeated heat treatment has been shown to induce oxidative adaptations in cell cultures and rodents, but similar work within human models is scarce. This study investigated the effects of 6 weeks of localized heat therapy on near-infrared spectroscopy-(NIRS) derived indices of muscle oxidative and microvascular function. Twelve physically active participants (8 males and 4 females, age: 34.9 ± 5.9 years, stature: 175 ± 7 cm, body mass: 76.7 ± 13.3 kg) undertook a 6-week intervention, where adhesive heat pads were applied for 8 h/day, 5 days/week, on one calf of each participant, while the contralateral leg acted as control. Prior to and following the intervention, the microvascular function was assessed using NIRS-based methods, where 5 min of popliteal artery occlusion was applied, and the reperfusion (i.e., re-saturation rate, re-saturation amplitude, and hyperemic response) was monitored for 2 min upon release. Participants also performed a 1-min isometric contraction of the plantar flexors (30% maximal voluntary contraction), following which a further 2 min interval was undertaken for the assessment of recovery kinetics. A 20-min time interval was allowed before the assessment protocol was repeated on the contralateral leg. Repeated localized heating of the gastrocnemius did not influence any of the NIRS-derive indices of microvascular or oxidative function ( p > 0.05) following 6 weeks of treatment. Our findings indicate that localized heating via the use of adhesive heat pads may not be a potent stimulus for muscle adaptations in physically active humans.

Six weeks of localized heat therapy does not affect muscle mass, strength and contractile properties in healthy active humans - Mariem Labidi; Mohammed Ihsan; Fearghal P. Behan; Marine Alhammoud; Tessa Smith; Mohamed Mohamed; Claire Tourny; Sébastien Racinais (European Journal of Applied Physiology, 2021)